2021
DOI: 10.3390/antibiotics10050561
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Klebsiella pneumoniae Associated with COVID-19

Abstract: Infections with carbapenem-resistant Enterobacteriaceae are emerging as an important challenge in healthcare settings. Currently, carbapenem-resistant Klebsiella pneumoniae (CRKP) are the species of CRE most commonly encountered in hospitals. CRKP is resistant to almost all available antimicrobial agents, and infections with CRKP have been associated with high rates of morbidity and mortality, particularly among persons with prolonged hospitalization exposed to invasive devices. We report nine patients hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…Co-infection with carbapenemase-producing K. pneumoniae in COVID-19 patients has been reported recently from Greece [ 50 ] and other countries. Invasive infections due to multidrug resistant KPC and/or OXA-48 carbapenemase-producing K. pneumoniae have been reported by Dumitru et al [ 58 ] in nine patients hospitalized in an intensive care unit (ICU) with severe COVID-19. Another review study by Medrzycka-Dabrowska et al [ 59 ] reported COVID-19 patients with carbapenem-resistant K. pneumoniae isolates from six countries—Italy, China, Egypt, United States, Spain and Peru—at a prevalence ranging from 0.35% to 53%.…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection with carbapenemase-producing K. pneumoniae in COVID-19 patients has been reported recently from Greece [ 50 ] and other countries. Invasive infections due to multidrug resistant KPC and/or OXA-48 carbapenemase-producing K. pneumoniae have been reported by Dumitru et al [ 58 ] in nine patients hospitalized in an intensive care unit (ICU) with severe COVID-19. Another review study by Medrzycka-Dabrowska et al [ 59 ] reported COVID-19 patients with carbapenem-resistant K. pneumoniae isolates from six countries—Italy, China, Egypt, United States, Spain and Peru—at a prevalence ranging from 0.35% to 53%.…”
Section: Discussionmentioning
confidence: 99%
“…resistance to the two antibiotic groups, could be responsible for the current situation in our ICU. Carbapenem-resistant Klebsiella infections in COVID-19 patients treated in ICUs have indeed been documented [13,14]. Knowing the mechanism by which resistance developed could be crucial in determining optimal infection control practices and new therapeutic options as the pandemic continues.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens such as carbapenem-resistant Enterobacteriaceae (CRE) and carbapenem-resistant Acinetobacter baumannii (CRA) have become hard to treat as carbapenems, the mainstay of both empiric and targeted therapy, are increasingly not fit for use [10]. This has become even more important during the pandemic, as outbreaks of both CRE and CRA are increasingly reported worldwide [11][12][13][14], affecting patient outcomes that are already compromised due to COVID-19. Because of these challenges, rigorous local surveillance is critical, as it enables continuous revisions of empiric therapy guidelines and improvement in antimicrobial stewardship, both for initiation of therapy and its de-escalation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the months of the early pandemic, controlling COVID-19 transmission and managing patients with COVID-19 effectively was emphasized, causing a shift of infection control and antimicrobial stewardship focus of care that, in turn, may have led to an increased incidence of MDRGNs colonization and infections [41]. A particular concern was caused by the increasing incidence of carbapenem-resistant Enterobacteriaceae (CRE) [42] and non-fermenting MDRGNs like carbapenem-resistant Acinetobacter baumannii (CRAB) [43] and Pseudomonas aeruginosa [44].…”
Section: Gram Negative Bacteriamentioning
confidence: 99%